Implementation of Perwakafan Law in Persyarikatan Muhammadiyah Sleman Regency - Abu Hanifah; Mohammad Syifa A. Widigdo; Muhsin Haryanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine: (1) Waqf legal products that have been issued within the Muhammadiyah Persyarikatan Muhammadiyah Sleman Regency, (2) Strategies/methods carried out by the Sleman Regency Muhammadiyah Association as Nadzir Waqf Legal Entities in administering and utilizing waqf land, (3) Management of waqf land in Persyarikatan Muhammadiyah Sleman Regency according to Islamic Shari'a and the applicable legislation in Indonesia. The type of research used is qualitative research, descriptive-analytic with an empirical-sociological approach. The research location is in Sleman Regency according to the work area of the Muhammadiyah Association of Sleman Regency. Data collection techniques using observation, interviews, and documentation. Based on the results of the research, the authors can conclude: (1) Persyarikatan Muhammadiyah Sleman Regency has carried out various innovations in the management and utilization of waqf land in Sleman Regency according to Islamic Shari'a and legislation in Indonesia, but what has been done is more a modification of the way in implementing Waqf Law, in this case the author has not found a specific or distinctive waqf legal product in Sleman Regency (2) Persyarikatan Muhammadiyah Sleman Regency as Nadzir Waqf performs its functions by planning, administering waqf assets, steps taken by certifying Muhammadiyah waqf land, securing it physically and physically social responsibility towards waqf assets, (3) Muhammadiyah Association of Sleman Regency in general has managed and utilized Muhammadiyah waqf land in accordance with Islamic Shari'a law and applicable laws and regulations in Indonesia, however, continuous efforts are still needed in in terms of improving the quality of human resources in the field of waqf, especially nadzir so that waqf is not only a vehicle for Muslims to worship but also can function for the welfare of Muslims.